The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cells9061440
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Single-Cell Technology in the Study and Control of Infectious Diseases

Abstract: The advent of single-cell research in the recent decade has allowed biological studies at an unprecedented resolution and scale. In particular, single-cell analysis techniques such as Next-Generation Sequencing (NGS) and Fluorescence-Activated Cell Sorting (FACS) have helped show substantial links between cellular heterogeneity and infectious disease progression. The extensive characterization of genomic and phenotypic biomarkers, in addition to host–pathogen interactions at the single-cell level, has resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 153 publications
(175 reference statements)
0
18
0
Order By: Relevance
“…Moreover, the advent of single-cell sequencing technology has provided researchers an attractive approach to deepen the understanding of cell-to-cell variation. This highly specialized method uncovers pathogen and host cell heterogeneity, which population studies incidentally masked due to the averaging of the results; single-cell analysis in dual-organism studies provides a critical component of understanding fungal infection and accelerates the development of novel therapeutics (126).…”
Section: Outlooks and Perspectivesmentioning
confidence: 99%
“…Moreover, the advent of single-cell sequencing technology has provided researchers an attractive approach to deepen the understanding of cell-to-cell variation. This highly specialized method uncovers pathogen and host cell heterogeneity, which population studies incidentally masked due to the averaging of the results; single-cell analysis in dual-organism studies provides a critical component of understanding fungal infection and accelerates the development of novel therapeutics (126).…”
Section: Outlooks and Perspectivesmentioning
confidence: 99%
“…For example, single-cell analysis of bacteria infected animal lung tissues was undertaken by first isolating immune and non-immune single cells for massively parallel single-cell RNA sequencing of host and bacterial mRNA. In depth analysis led to the identification of infected cells without the presence of contaminating bystander cells, determination of bacterial loads and gene expression profiles of both host and pathogen [54].…”
Section: Single Cell Rna Sequencingmentioning
confidence: 99%
“…Moreover, the authors showed the rate of heterogeneity in 2D and 3D cultures and in solid-tumour. Lin et al [5] investigated how single-cell technology has been applied to inspect several infectious diseases. They studied how cellular heterogeneity is linked substantially with the progression of infectious disease using fluorescence-activated cell sorting and next-generation sequencing.…”
mentioning
confidence: 99%
“…Again, bulk analysis of millions of cells cannot explore cellular heterogeneity characteristics and dynamics at the molecular level, in a particular cell populations [ 2 , 3 , 4 ]. However, the investigations on the progress of any disease have remained challenging because of the physiological states of cells and heterogeneity nature of cells in a specific given population [ 2 , 3 , 4 , 5 ]. Compared to the average analysis of millions of cells together in bulk, single-cell analysis (SCA), provides clear information about each cell, such as specific biological factors of cell, which is helpful to understand stem cells behaviour or tumour progression [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation